Enhanced unscented transform method for probabilistic load flow studies - Oke, Oluwabukola A. (2013)
The advent of deregulated electricity and the call for sustainable energy practices are major drivers for the continued increase of renewable energy systems within the modern day power network. Dominant among them is the wind energy system whose output is uncertain because of its dependence on the prevailing climatic conditions. This increases the level of uncertainty witnessed within the power system as such, as the penetration of renewable energy systems continue to increase, their effects cannot be trivialised.